HUBUNGAN ASUPAN ENERGI DAN GIZI MAKRO SERTA STATUS GIZI PADA PASIEN PRE-EKLAMSI DI RSIA SITI FATIMAH KOTA MAKASSAR - Rudy Hartono; Hikmawati Mas'ud; Andi Syam Haeru (Politeknik Kesehatan Makassar, 2017)
Preeclampsia until now is still a health problem that can not be solved completely. Statistical data in developed countries shows that 10-30% of all maternal deaths are caused by preeclampsia. Preeclampsia is one of the three major causes of maternal death in addition to bleeding and infection. Nutritional intake is an indicator to see the nutritional adequacy and upper arm circumference of pregnant women is one tool to assess the nutritional status, so it can be known complications during pregnancy. This study aims to determine how the relationship of energy intake and macro nutrition and nutritional status with the incidence of preeklamsi in RSIA Siti Fatimah Makassar. The type of this research is cross sectional study. Data collection was done by interview using questionnaire with total sample as many as 34 people. The result of the research using statistical analysis of chi-square test showed that energy intake, protein intake, fat intake, and carbohydrate intake as well as nutritional status were obtained by p values, p = 0.584, p = 0.611, p = 0.416, p = 0.649 And p = 0.547 means that there is no relationship between energy intake and macro nutrition and nutritional status in patients preeklamsi in RSIA Siti Fatimah Makassar. It is expected that the respondent health officer can increase the frequency of counseling both personally and group related factors that can influence the occurrence of preeclampsia.Keywords : Intake of Energy, Macro Nutrition, Nutrition Status, Preeclampsy